The Effect of Electronic Word of Mouth (E-WOM) and Online Customer Reviews on Purchase Decisions for Azarine Products on TikTok Shop - Khodijah, Ria; Zahara, Anzu Elvia (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The increasing use of TikTok Shop as a social commerce platform has transformed how consumers access product information and make purchasing decisions, particularly in the beauty and skincare industry. However, research specifically examining the role of electronic word of mouth and online customer reviews in purchase decisions for Azarine products on TikTok Shop remains limited. This study aims to analyze the effects of electronic word of mouth and online customer reviews on purchase decisions for Azarine products among consumers in Jambi City. A quantitative approach with a survey design was employed, involving 96 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed through multiple linear regression. The findings indicate that electronic word of mouth has a positive and significant effect on purchase decisions. Online customer reviews also have a positive and significant effect on purchase decisions. Simultaneously, both variables significantly influence consumers’ purchase decisions. These findings contribute to the digital marketing literature by highlighting the strategic role of consumer-generated information in shaping purchasing behavior within social commerce contexts. The study concludes that positive electronic word of mouth and credible online customer reviews are essential factors in strengthening consumer confidence and encouraging purchase decisions. Practically, the findings suggest that Azarine and other local skincare brands should actively manage consumer-generated content to enhance trust, visibility, and purchasing intention on TikTok Shop.